Metalimnetic chlorophyll maxima in Lake Kinneret ‐ Chlorobium revisited. (27th November 2020) - Ninio, Shira; Lupu, Achsa; Eckert, Werner; Ostrovsky, Ilia; Viner Mozzini, Yehudit; Sukenik, Assaf
Abstract: A deep chlorophyll maximum (DCM) is often seen in stratified freshwater bodies at the interface between an anaerobic layer and an oxic layer. A DCM of the green sulfur bacterium Chlorobium phaeobacteroides was previously reported as a dense population in the oxygen devoid layer of a monomictic stratified lake, Lake Kinneret, Israel. In this multidisciplinary study, we examined the vertical distribution and diversity of the DCM photosynthetic community and characterised it spectrally and genetically, over two consecutive years. Pigment composition, together with 16S rDNA sequencing data unveil the presence of more than a single Chlorobium species as dominant members of the DCM community. Altogether, five different Chlorobia genotypes were identified, four of which occurred in both of the studied years. Phylogenetic analysis suggests that the dominant genotype is closely related to C. phaeobacteroides, implying that it contributes the majority of the bacteriochlorophyll‐ e found in the DCM of the lake. Hierarchical clustering analysis demonstrates that dissolved oxygen concentration is a strong predictor for the distribution of all Chlorobia genotypes found in Lake Kinneret. Furthermore, this analysis suggests that competition probably exists between the various Chlorobia genotypes and proposes that a C. phaeobacteroides ‐related amplicon sequence variant is better equipped to cope with the conditions prevailing in Lake Kinneret metalimnion. Chlorobia genotypes composing the DCM appear at a similar relative abundance in two consecutive years, even though timing and intensity of the DCM were different. This stable structure of the Chlorobia community observed here may represent a general theme in other stratified freshwater bodies harbouring Chlorobia .